Domestic sourcing vs. cross-border sourcing: Impact of the quality of the scrap metal and Government's tariff policies. (20th January 2019) - Niu, Baozhuang; Liu, Yaoqi; Luo, Huajiang; Feng, Beibei
Abstract: It is optional for a non-ferrous original equipment manufacturer (OEM) to rely on a domestic contract manufacturer (CM) for metal material purchasing and manufacturing services. It is also optional for an OEM to purchase scrap metal abroad due to the government's encouragement, although the OEM suffers from quality uncertainty of the scrap metal, and still need rely on the CM for processing and manufacturing services. In this paper, we characterize the tradeoffs between economics sustainability and environmental sustainability from the perspectives of the OEM, the CM and the government. First, we derive threshold policies for the OEM to select the sourcing strategies, with respect to the quality of the scrap metal. Then, we analyze the supply chain parties' alignment opportunities of their preferences over the OEM's sourcing strategies. Interestingly, we find that win-win situations exist when (1) the quality of the scrap metal is high and the CM's procurement cost is high (both the OEM and the CM prefer cross-border sourcing), and (2) the quality of the scrap metal is low and the CM's procurement cost is low (both OEM and the CM prefer domestic sourcing). Regarding the government, we find that it would encourage the OEM's cross-border sourcing to maximize the social welfare if one of the following conditions is satisfied: (1) the environmental concern is low and the quality of the scrap metal is high; (2) the environmental concern is high and the quality of the scrap metal is low. If the government wants to save domestic resource, CS is always prefered.